Prevention of Criminal Acts of the Drug Trade Through the Internet Media Based on Positive Law in Indonesia - Hasibuan, Edi Saputra; Clara Ignatia Tobing (Dinasti Research, 2022)
The era of Technology 4.0 triggers the emergence of a recent pattern in society known as the digital economy in the people's daily buying and selling process. The digital economy itself adopts the use of information and communication technology innovations that give rise to a variety of products, production processes and new services. Changes in the process of producing goods and distributing them become critically dependent on the use of information technology and electronic media. One of the goods that has experienced a shift in distribution is narcotics. Narcotics transactions are facilitated via online and payment via transfer, so that sellers and users do not need to meet face-to-face to conduct transactions. The legal vacuum of online narcotics transactions causes Indonesia to not yet have a complete and clear legal rule regarding the eradication of narcotics through cyberspace. This study aims to analyze the existing legal regulations in Indonesia for narcotics offenders and providers. Through this research, it is expected to obtain a legal vacuum in the narcotics trade through the internet and provide ideas and ideas to fill this void.